Effects of paddles and fins on front crawl kinematics, arm stroke efficiency, coordination, and estimated energy cost - De Matos, C. C.; Guignard, B.; Castro, F. De Souza; Guimard, A. (Frontiers in Physiology, 2023)
Paddles and fins are used in swimmers training with different objectives (e.g., increase propulsive areas of hands and feet, improve the feeling of water flow). These artificial modifications of the stroke might be viewed as external constraints of the stroke task, both will either disturb or facilitate swimming modalities, so the coaches should manipulate its use to extract benefits for performance. This study seeks to investigate the precise effects of wearing either paddles(PAD) or fins(FINS) vs. a no-equipment(NE) trial in three all-out front crawl exercises on swimmer kinematics, arm stroke efficiency(ηp), upper-limbs coordination patterns (Index of Coordination, IdC), and estimated energy cost(C). Eleven regional to national-level male swimmers participated in the study (age: 25.8 ± 5.5 years, body mass: 75.2 ± 5.5 kg, height: 177 ± 6.5 cm) and were recorded from both sides of the swimming pool to collect all variables. Repeated measures ANOVA and Bonferroni post-hoc were used to compare the variables. Effects sizes were calculated. Time to cover the distance and velocity were higher in FINS swimming, with larger values of stroke length(SL) and lower kick amplitude in comparison to the other trials(PAD and NE). The use of FINS also modified the stroke phases durations by presenting significant lower propulsion time during the stroke in comparison to PAD or NE. Values of IdC were lower (IdC < -1%, so catch-up pattern of coordination) for FINS in comparison to NE. In terms of ηp, using PAD or FINS demonstrate higher arm stroke efficiency than swimming without equipment. Finally, C was significantly higher in FINS swimming in comparison to NE and PAD. From the present results, it should be noted that the use of equipment such as fins deeply modify the structure of the swimming stroke (from the performance-related parameters through the kinematics of both upper and lower limbs to the stroke efficiency and coordination pattern). So, using equipment should be appropriately scaled by the coaches to the objectives of the training session in swimming, and in emergent sports such as “SwimRun”, paddles and fins must be viewed as tools to achieve higher velocities to cover a given distance.